Predictors of beginning teachers’ teaching performance - Bacus, Remedios C.; Picardal, Marchee T.; Perez, Noremay B.; Balo, Vincent Theodore M. (Frontiers in Education, 2024)
IntroductionQuality education hinges on teacher quality. The multifaceted nature of teachers’ roles and their teaching performance necessitates a comprehensive exploration of factors influencing overall education quality.MethodsThis study employed a regression research design, utilizing an expert-validated survey questionnaire completed by 2,680 beginning teachers from the Department of Education across 16 regions in the Philippines. The study aimed to identify personal, educational, and professional characteristics that predict teaching performance as measured by the Results-based Performance Management System (RPMS).ResultsThe analysis revealed that among various characteristics, socioeconomic status (personal), grade point average (educational), and both the grade level taught and length of service (professional) were significant predictors of teaching performance.DiscussionThe findings underscore the need for teacher education institutions to adapt curricular delivery in a manner that reflects the practical realities of teaching and acknowledges situated learning. Recommendations include the development of quality assurance mechanisms, academic coaching and mentoring programs, and initiatives to strengthen financial literacy among pre-service teachers to enhance their future teaching performance.